ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) PERFORMANCE AND CORPORATE VALUE: UNPACKING THE MODERATING EFFECT OF COMPANY SIZE - Mulyana, Dendi; Widyaningsih, Aristanti; Rozali, Rozmita Dewi Yuniarti (Jurnal Ekonomi dan Bisnis Airlangga, 2025)
Introduction: This study endeavours to analyse the effect of environmental, social, and governance (ESG) performance on corporate value and determines whether company size can affect this outcome. Methods: This quantitative research was conducted across five Southeast Asian (ASEAN) countries over four periods, from 2020 to 2023. The sample comprises 361 companies, selected using a purposive sampling technique, resulting in a total of 1,444 observations. The study employs moderated regression analysis (MRA) of panel data. Results: The findings reveal that ESG performance unfavourably affects corporate value. However, company size mitigates this unfavourable effect, as evidenced by its substantial favourable moderating role. Further analysis at the country level shows consistent results in Indonesia, Malaysia, and Thailand. In contrast, ESG performance does not substantially affect corporate value in Singapore and the Philippines, nor does company size have a notable moderating effect. Conclusion and suggestion: This study underscores the significance of integrating ESG policies into corporate strategies, especially for larger corporations. Smaller firms may need to focus on cost-effective initiatives or seek support to scale their ESG efforts. For policymakers, the study underscores the necessity of enhancing support through transparency, fiscal incentives, and regulations to promote ESG awareness and implementation, particularly in countries where the effect of ESG is limited.